ADAPTABILITY OF SOME POTATO CULTIVARS IN NORTH GUJARAT - Patel, R. N; Patel, N. H; Pandey, S. K.; Patel, J. M.; Kanbi, V. H; Patel, C, K. (Potato Journal, 2013)
Eight potato cultivars were studied for the three adaptability parameters (gi, bi and S2di) of yield at early harvest (75 days) and full maturity (90 days) at Deesa and Ladol in North Gujarat during rabi 1999, 2001 and 2002. Genotype S Environment interaction was significant for both the harvests. Non-linear component was predominant in genotype S environment (G S E) interaction for both the harvests. A simultaneous consideration of the three parameters for high yield at early harvest (75 days) showed Kufri Pukhraj to have wide adaptability, whereas Kufri Badshah and Kufri Jawahar were adapted to favourable environment only. However, in main season crop (90 days harvest), Kufri Badshah was found ideally stable.